Cross-talk between aging resilience pathways and autoimmunity onset - Mittal, Rahul; Saavedra, Danay; Mittal, Mannat; Hirani, Khemraj (Frontiers in Immunology, 2025)
Aging and autoimmunity intersect through the progressive decline of resilience pathways that maintain physiological stability. Resilience refers to the integrated capacity of molecular, cellular, and systemic mechanisms to repair damage, adapt to stress, and preserve immune tolerance. With advancing age, resilience deteriorates due to chronic inflammation, cellular senescence, epigenetic drift, and metabolic dysfunction. While a wide spectrum of autoimmune diseases exists, this perspective focuses primarily on those that emerge or progress with advancing age, in which a decline in immune resilience rather than congenital immune defects plays the predominant role. These changes weaken adaptive capacity and promote conditions that allow autoreactive lymphocytes to persist, initiating autoimmune pathology. This perspective frames autoimmunity as a sentinel manifestation of resilience collapse rather than an isolated failure of immune tolerance. The objective of this article is to delineate the shared molecular and systemic mechanisms by which age-associated loss of resilience promotes autoimmune susceptibility, and to highlight how this framework can guide both research priorities and therapeutic innovation. By examining convergent pathways across inflammation, senescence, epigenetics, and metabolism, we emphasize that autoimmune disease arises from integrated failures in the networks that sustain homeostasis. Recognizing these connections enables the development of integrated biomarkers to detect resilience decline and identify individuals at risk before clinical onset. It further supports therapeutic strategies aimed at enhancing repair capacity, maintaining immune tolerance, and restoring adaptive responses. Recasting autoimmunity in this framework provides opportunities for preventive interventions and novel treatments with the potential to extend healthspan.